2003
DOI: 10.1089/104303403766682232
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Capacity of a Dominant-NegativeRETProto-Oncogene Mutant in a Medullary Thyroid Carcinoma Model

Abstract: Gain-of-function mutations in the RET proto-oncogene resulting in a constitutively active receptor tyrosine kinase have been identified as responsible for three subtypes of multiple endocrine neoplasia type 2 (MEN-2) and the development of sporadic medullary and papillary thyroid carcinoma. An important strategy in cancer gene therapy is the inhibition of oncogenic signal transduction by interfering with the molecular mechanisms of activation. In the present study, we tested the therapeutic capacity of an aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…Molecular mimicry has been shown using in vitro models to inhibit constitutively active RET [50]. Dominant negative RET mutants may have a future role in the treatment of MTC: these mutant proteins can dimerize with oncogenic RET molecules, resulting in the retention of the protein complex in the endoplasmic reticulum, blocking transduction and/or ultimately leading to increased apoptosis [51].…”
Section: Ongoing Challenges and Unmet Needsmentioning
confidence: 99%
“…Molecular mimicry has been shown using in vitro models to inhibit constitutively active RET [50]. Dominant negative RET mutants may have a future role in the treatment of MTC: these mutant proteins can dimerize with oncogenic RET molecules, resulting in the retention of the protein complex in the endoplasmic reticulum, blocking transduction and/or ultimately leading to increased apoptosis [51].…”
Section: Ongoing Challenges and Unmet Needsmentioning
confidence: 99%
“…Evidence for its suitability as a target comes from suppression of oncogenic RET in a thyroid carcinoma model system by small molecule inhibition (35) as well as from the beneficial effect of a dominant-negative RET mutant in MTC cells blocking tumor growth (36). Small molecule inhibitors of protein kinases have already been proven clinically useful for a variety of human diseases (37,38).…”
mentioning
confidence: 99%
“…Drosten et al [91] reported that adenovirus-mediated transduction of dominant negative RET into TT cells reduced expression of oncogenic RET receptors on the cell surface. They also reported that inoculation of dominant negative RET-expressing MTC cells into nude mice led to an almost complete suppression of tumor growth [91,92]. These results suggest that inhibition of oncogenic RET expression by a dominantnegative RET mutant is an effective approach for MTC treatment, although many issues remain to be resolved before viral vectors can be used in vivo.…”
Section: Other Strategies To Inhibit Retmentioning
confidence: 97%